Design and Analysis of a Chuck-type Adjustable Diameter Continuously Variable Transmission - Ning Mei; Aiping Song; Chenwei Yu (Jixie chuandong)
A new structure of chuck-type adjustable radius pulley continuously variable transmission (CVT) is proposed. The new CVT uses the belt drive mode of the combination of the chuck-type adjustable radius pulley and the multi-wedge belt in the drive, and the face contact friction drive between the pulley and the drive belt is realized. The calculation formula of the effective circumferential force of the chuck-type adjustable radius pulley drive is deduced, and the variation law of the maximum effective circumferential force of the chuck-type adjustable radius pulley is analyzed, which verifies the drive ability of the chuck-type adjustable radius pulley with large torque. In addition, the dynamics simulation based on Adams is carried out, and the experimental device of chuck-type adjustable diameter CVT is developed to test and verify. The results show that the drive speed of the new CVT is stable and meets the requirements of vehicle use.